A Comparative Study of Amrita Guggulu and Siravyadha in the Management of Siragranthi w.s.r to Varicose Vein - Akhila, A R; Sharma, Vishnu Dutt; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2024)
The study entitled “A Comparative Study Of Amrita Guggulu And Siravyadha In The Management Of Siragranthi W.S.R To Varicose Vein” is mainly based on clinical observation. Susruta explained the nidanas, samprapthi, chikitsa, and sadhyasadhyatha, as well as many forms of therapies and consequences that were gathered from various classical sources. The study includes the use of Amrita guggulu internally and Siravyadha procedure. A total of 50 cases of varicose veins were chosen and are randomly separated into two groups. For three months, Amrita guggulu two tablets twice daily after food were administered. Siravyadha was performed twice, once on the first day and again on the 90th day. Pain, nocturnal cramps, itching, ankle flare, venous edema, venous induration, and skin pigmentation were all observed in all of the study participants. After treatment procedure Siravyadha reduction in symptoms like pain, itching, varicosities and discoloration was statistically significant with the p value of< 0.001 was observed. One Patient in Group A (Amrita guggulu) and three patients of group B ( Sirayadha) got maximum improvement. 12 patients in group A and 15 patients in group B got moderate improvement.